Ethnobotanical and Biochemical Data Bring no Evidence to Clarify the Biosystematics of Irvingia gabonensis and I. wombolu (Irvingiaceae): A Review - Vihotogbé, Romaric L.; Vihotogbé-Sossa, Carole; AKISSOE, H. NOËL (My University, 2023)
Irvingia gabonensis and I. wombolu are two Irvingiaceae species with economic significance, because of their valuable kernels for West and Central Africans to thicken sauces. They are called sweet/edible – and bitter/inedible – fruited African bush mango trees (ABMTs), respectively, because of the taste of their mango – like fruit. The striking difference in fruit pulp taste clearly discriminates between Irvingia gabonensis and I. wombolu trees, which are morphologically very similar. Experts profoundly disagree on the taxonomic significance of differences among bush mango trees to allow classification of Irvingia gabonensis and I. wombolu as clearly different species. Therefore, the random species or variety consideration in researches indicates difficulty to define taxonomic units, which is vital for effective conservation and use of ABMT germplasm, because the source of tree – to tree variations is uncertain. This paper reviews ethnobotanical and biochemical data on ABMTs in order to evaluate their contribution to the biosystematics of I. gabonensis and I. wombolu. Thus, information on local uses (food and medicinal applications) and biochemical data of the kernel, pulp, leaves and bark are compared, and their implications for the distinction between I. gabonensis and I. wombolu are discussed. We evidenced a lack of comparative data related to ethnobotanical and many phytochemical aspects, mostly on the bark, leaves and roots. We hypothesised obvious misidentifications causing conflicting patterns, but no evidence of any phytochemical dissimilarity was found between I. gabonensis and I. wombolu. Kernel macronutrient composition, diversity, types and abundance of fatty acids in the kernel oil and the functional and therapeutic properties of this oil do not allow to discriminate between both species. Moreover, there is no correlation among patterns of lipophilic components profile, composition in fatty acids in the oil, geographical distribution of ABMTs. We interpreted these random patterns within ABMTs as tree – to – tree variations and this explains the vast co-occurrence of both taxa. However, consistent differences in fruit pulp taste across contrasting ecological conditions imply significant phytochemical differentiation between I. gabonensis and I. wombolu. This needs to be thoroughly re-evaluated and correlation with genetic data will clarify the taxonomic issue.
Keywords: biodiversity; biochemical species distinction; human nutrition; Irvingia spp; biosystematics; Sub-Saharan Africa